Architectural Imaginaries: From Nomadism to the Volunteer Prisoners of Architecture - Muniz Ribeiro, Diego Mauro (Bitacora Arquitectura, 2017)
The present study deals with changes in the architectural imaginary between the late 1950s and early 1970s, especially with regard to the promises of unrestrictedmobility (architecture and technology in favor of a society that would know no frontiers) and the subsequent representations, in which architecture not only continues to perpetuate exclusion and regimes of segregation, but also assigns a desirable status to this process.